1992
DOI: 10.3904/kjim.1992.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Prostaglandin E2 in Gastric and Duodenal Mucosa: Possible Role in the Pathogenesis of Peptic Ulcer

Abstract: BackgroundProstaglandin E which is present abundantly in the gastric mucosa is a powerful inhibitor of gastric acid secretion and a stimulus to gastric mucus production. In addition, prostaglandin E2 inhibits ulcer formation in animals, and the synthetic analogues of prostaglandin E have successfully been used in the treatment of patients with gastric and duodenal ulcer disease. To evaluate the role of endogenous prostaglandin E2 in the pathogenesis of the peptic ulcer disease, we measured mucosal prostaglandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We found that basal and both forskolin-and PGE 2 -stimulated duodenal mucosal bicarbonate secretion was markedly diminished in ovariectomized mice. In humans, PGE 2 was a major product produced by the duodenal mucosa (Konturek et al 1981;Hillier et al 1985;Aly et al 1987;Park et al 1992). The results demonstrate that oestrogen upregulates the functional activities of CFTR and SLC26A6, which contributes to explaining the sex difference in duodenal mucosal bicarbonate secretion.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We found that basal and both forskolin-and PGE 2 -stimulated duodenal mucosal bicarbonate secretion was markedly diminished in ovariectomized mice. In humans, PGE 2 was a major product produced by the duodenal mucosa (Konturek et al 1981;Hillier et al 1985;Aly et al 1987;Park et al 1992). The results demonstrate that oestrogen upregulates the functional activities of CFTR and SLC26A6, which contributes to explaining the sex difference in duodenal mucosal bicarbonate secretion.…”
Section: Discussionmentioning
confidence: 76%
“…In various species, gastric and duodenal mucosae were found to be capable of generating large mounts of PGE 2 (Ahlquist et al 1982;Aly et al 1987;Kapicioglu et al 1990). In humans, PGE 2 was a major product produced by the duodenal mucosa (Konturek et al 1981;Hillier et al 1985;Aly et al 1987;Park et al 1992). In physiological conditions, gastric acid is an important stimulant of proximal duodenal mucosal bicarbonate secretion (Allen & Flemström, 2004;Konturek et al 2004), and studies have demonstrated that endogenous PGE 2 is the most important intramucosal mediator of gastric acid-stimulated duodenal bicarbonate secretion (Bukhave et al 1990;Takeuchi et al 1999;Sugamoto et al 2001).…”
Section: Discussionmentioning
confidence: 99%